Eumycetoma of the Foot in a 70‐Year‐Old Male Farmer - Allahdad Khan; Saad Masood; Aseel Kamal (Clinical Case Reports)
ABSTRACT Clinicians should consider eumycetoma, actinomycotic mycetoma, and skin cancers in patients from tropical or subtropical regions who present with painless swelling and discharging sinuses. The early histopathology, microbiological studies in conjunction with imaging, are of critical importance in narrowing the differential and starting appropriate treatment to prevent complications and deformities.